Levoatriocardinal Vein: An Unusual Cause of Right-to-Left Shunting - Shet, Nilima; Maldjian, Pierre
We present a case demonstrating an anomalous vessel connecting the left brachiocephalic vein and the left superior pulmonary vein, found incidentally on computed tomography (CT) imaging. This pulmonary–systemic venous connection, known as a levoatriocardinal vein, is a rare anomaly. In previous descriptions, this vessel has typically been associated with left-to-right shunt. Here, we describe the magnetic resonance imaging (MRI) and CT findings in a case with right-to-left shunting through the anomalous vessel likely secondary to elevated right cardiac pressure.